Influencing Factors of 2D Shear Wave Elastography of the Muscle – An Ex Vivo Animal Study - Rominger, Marga B; Kälin, Pascal; Mastalerz, Monika; Martini, Katharina; Klingmüller, Volker; Sanabria, Sergio; Frauenfelder, Thomas (Ultrasound International Open, 2018)
To evaluate measurement confounders on 2D shear wave elastography (2D-SWE) elastography of muscle.Ex vivo, porcine muscle was examined with a GE LOGIQ E9 ultrasound machine with a 9 L linear (9 MHz) and C1-6 convex probe (operating at 2.5 or 6 MHz). The influence of different confounders on mean shear wave velocity (SWVmean) was analyzed: probes, pressure applied by probe, muscle orientation, together with the impact of different machine settings such as frequency, placement depth and size of region of interest (ROI). The mean of twelve repeated SWVmean measurements (m/s) and coefficient of variation (CV; standard deviation/mean in %) were assessed for each test configuration. Reproducibility (CV) and maximum possible tissue depth of the linear probe were inferior to the convex probe. With the linear probe, there was a linear decrease of SWVmean with placement depth from 4.56 m/s to 1.81 m/s. A significant increase of SWVmean (p<0.001) was observed for larger ROI widths (range 3.96 m/s to 6.8 m/s). A change in the machine operation mode ('penetration' instead of 'general') led to a significant increase of SWVmean (p=0.04). SWVmean in the longitudinal direction of muscle was significantly higher than in cross section (p<0.001) (e. g. 4.56 m/s versus 3.42 m/s). An increase of linear probe pressure significantly increased muscle SWVmean from 5.29 m/s to 7.21 m/s (p<0.001). 2D-SWE of muscle is influenced by a wealth of parameters. Therefore, standardization of measurement is advisable before application in clinical research studies and routine patient assessment.
Keywords: muscular; soft tissues; ultrasound; ultrasound 2D